1999
DOI: 10.1074/jbc.274.35.24906
|View full text |Cite
|
Sign up to set email alerts
|

Trench-shaped Binding Sites Promote Multiple Classes of Interactions between Collagen and the Adherence Receptors, α1β1 Integrin and Staphylococcus aureus Cna MSCRAMM

Abstract: Although the S. aureus and human proteins have unrelated amino acid sequences, secondary structure composition, and cation requirements for effective ligand binding, both proteins bind at multiple sites within one collagen molecule, with the sites in collagen varying in their affinity for the adherence molecule. We propose that (i) these evolutionarily dissimilar adherence proteins recognize collagen via similar mechanisms, (ii) the multisite, multiclass protein/ligand interactions observed in these two system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 51 publications
6
80
0
Order By: Relevance
“…3 Furthermore, other integrins also bind to multiple binding sites within their cognate ligands. Previous studies demonstrated that ␣ 1 Iand ␣ 2 I-domains, the ligand binding domains of integrins ␣ 1 ␤ 1 and ␣ 2 ␤ 1 , respectively, bound to multiple binding sites in collagen type 1 (28,29). Although integrins ␣ 1 ␤ 1 and ␣ 2 ␤ 1 are not established as multiligand receptors, these studies convincingly demonstrated that a single integrin can bind to several sites within the same ligand.…”
Section: Discussionmentioning
confidence: 79%
“…3 Furthermore, other integrins also bind to multiple binding sites within their cognate ligands. Previous studies demonstrated that ␣ 1 Iand ␣ 2 I-domains, the ligand binding domains of integrins ␣ 1 ␤ 1 and ␣ 2 ␤ 1 , respectively, bound to multiple binding sites in collagen type 1 (28,29). Although integrins ␣ 1 ␤ 1 and ␣ 2 ␤ 1 are not established as multiligand receptors, these studies convincingly demonstrated that a single integrin can bind to several sites within the same ligand.…”
Section: Discussionmentioning
confidence: 79%
“…Our data strongly support the LAIR-1 putative collagen-binding region and lend support to the possibility that GPVI and other collagen-binding members of the LRC may use a wide trench region on the Ig-like domains flanked by CC′-and FG-loops to bind to collagen. This hypothesis regarding binding topology mirrors a more general prediction about collagen-protein interaction made more than 15 y ago, which predicted that the diversity of residues encoded in such trenches may confer specificity to certain types or regions of collagens (30).…”
Section: Discussionmentioning
confidence: 99%
“…3b,c). Furthermore, in contrast to their unique tandem arrangement, the individual domains show a high structural homology to other VWA domains, like the A3 domain of human von Willebrand factor 23 or the I-domains of Integrin a1 and a2 19,20 (Fig. 3d-f), despite an only moderate sequence identity ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2e; Supplementary Table 1), demonstrating the stability of the relative domain arrangement. The two structures only differ in the length of a single a-helix (a6, numbering of the secondary structure elements according to published VWA domain structures 19,20,23 , see also Supplementary Fig. 2), which is three amino acids longer in crystal form 1 (residues 226-241) than in crystal form 2 (residues 229-241).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation